Left behind in the race to the top : realities of school reform - Gorlewski, Julie A.; Porfilio, Brad (Emerald Publishing Limited : Information Age Pushing, Inc., 2013)
Public education is suffering attacks that are well funded and extraordinarily complex and multifaceted. These conditions make it difficult for educators and citizens to gather the information they need to mount meaningful resistance, especially since mainstream media tends to be uncritically supportive of neoliberal reforms. The Orwellian language of reforms is adopted and promoted through news outlets, politicians, and film; thus, arguments against these reforms must bubble up through social media and alternative outlets. By providing a coherent, comprehensive description of contemporary neoliberal initiatives and analyzing their effects on students, teachers, administrators, and teacher education, this book will allow educators, parents, students, and citizens to strengthen their resolve to save public education and, potentially, work to preserve the promise of democracy.This book examines and uncovers the effects of standardization and privatization on public education. Contributors consider the how of standardized curriculum and assessment, coupled with philanthropic and corporate pressure, have influenced the experiences of students, parents, and teachers. Divided in sections entitled Testing, Testing; Privatization and Militarization: Redefining Schools; Alienation: Displacing Students and Teachers; and Resistance: Opting Out and Hope for Change, this text offers a combination of information and inspiration for teachers, teacher educators, policymakers, parents and anyone interested in understanding the current state of public education.